Bimetallic organic framework NiFeMOF driven by tiny Ag particles for PVDF dielectric composites. (August 2021) - Guan, Lizhu; Weng, Ling; Chen, Nan; Kannan, Haripriya; Li, Qiong; Zhang, Xiaorui; Wu, Zijian; Ma, Yingyi; Sahu, Ayaskanta
Highlights: A new class of Ag@NiFeMOF 2D ferroelectric hybrid nanoplates has been synthesized by a two-step method. The discharge energy storage density of the composites reaches 8.01 J/cm 3 (η = 64%), which is 6.1 times higher than that of the pure membrane. The bimetallic NiFeMOF exhibits a stronger electric dipole moment than the monometallic NiMOF under the strengthening effect of Ag particles. The Ag-induced Coulomb blocking effect in NiFeMOF nanoplates inhibits the migration of electrons, improves the electric breakdown strength. Abstract: Two-dimensional (2D) anisotropic ferroelectric nanoparticles are considered as potential candidates in polymer-based dielectric energy storage materials. We successfully synthesized a new class of Ag@NiFeMOF 2D ferroelectric hybrid nanoplates and added it to PVDF matrix to prepare Ag@NiFeMOF/PVDF composites (MOF = metal-organic framework). The morphology of composites reveals that Ag atoms are uniformly dispersed in the nanoplates as 14 nm clusters. The discharge energy storage density of composites shows a remarkable improvement of over 610% compared to the pure PVDF sample and reaches a value of 8.01 J/cm 3 (η = 64%). We hypothesize that the bimetallic NiFeMOF exhibits a stronger electric dipole moment than the monometallic NiMOF under the strengthening effect of Ag particles, which improves the polarization ability of composites. In addition, under high electric field strength, the Ag-induced Coulomb blocking effect in NiFeMOF nanoplates inhibits the migration of electrons, improves the electric field breakdown strength, and thereby increases the energy storage ability of the composites.